Estado, movimentos sociais e as teias históricas da sustentabilidade no desenvolvimento do Norte de Minas nos anos 1990 - Leite, Valéria de Jesus (2016)
This thesis aims analyze the regional development process from North of Minas Gerais and its implications for workers from 1970 to 2000. Our main aim was understand the forces\' relations that have been fought in this process by focusing, especially the conflicts, the confrontations in the relations established between the various groups and social classes to understand the \"peculiarities\" of the region. For that, we analyzed the voices at first presented as a discordant of this process, and how they have conducted the contestation actions of the development project headed by the local bourgeoisie, and was mainly through the notion of sustainable development. Thus, we see how the entities that supported the workers have organized to dispute space in the regional development process, especially the Sustainable Regional Development Forum, made in 1993. Thus, it was possible to know their proposals and analyze their actions in a moment when SUDENE\'s policies were already reality in the region. The individuals chosen to direct this research were the organizations that sought to speak for the workers, therefore, non-governmental and pastoral organizations of the Catholic Church, of which we elect the Pastoral Local Commission (CPT) and Alternative Agriculture Center of northern of Minas Gerais. (CAA ). This perspective, we seek to evaluate whether there was popular participation, how it happened, and to which extent the social movements were present and which agents and agencies have been active in this process. The theoretical and methodological option for the construction of this research privileges authors from the Marxist tradition, they helped us to think about the political and economic articulated with the social. Thus, the reflections of authors such as EP Thompson and Antonio Gramsci are present in this research as guiding principles, that is, as a means to operationalize and discuss our underlying assumptions and goals. The sources used in this study were varied. Due to the difficulty of finding the records produced by the workers, we privilege some documents made by the entities that supported them, as the papers of the CEBs. Besides these we use reports, correspondence, booklets, pamphlets, studies, oral reports, magazines, newspapers, reports from the Regional Public Hearings, criminal cases, among others. From this material it was possible to understand and explain part of the process that we propose to investigate.